Pelas ruas de Goiânia : evocando lendas urbanas como patrimônio imaterial (2000-2023) - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This study aims to survey the urban legends of Goiânia, Goiás, from a heritage perspective. The objective is to collect the legends of Goiânia in order to map the city with these stories, eventually creating opportunities for interventions in the area of macabre tourism. The outcome of this research will be a tourist guide for Goiânia, featuring a mapping of these legends, along with their documentation, which will be important for preserving the narratives that are traditionally passed down orally. To rethink these narratives, we will consider the location, the “entity,” and the source of the records, grounding our approach in concepts of memory and the relationship between intangible heritage and death, drawing from the works of Chuva, Abreu, and Chagas. To address urban legends as dark heritage, we will reference authors Meneguello, Foley, and Lenon. The methodology employed will be duration ethnography, based on Eckert’s work, supported by a culturalist approach and mixed research instruments, including questionnaires. Through the questionnaire, we aim to identify the relationship and knowledge of the local population regarding the urban legends. The identification of the legends will be conducted using databases such as the Capes Journal Portal, Google Scholar, and websites of Goiás newspapers, the time frame of the reasearch was from 2000 - 2023.
Through the streets of Goiânia : evoking urban legends as intangible heritage (2000-2023)
Keywords: Patrimônio; Lendas; Urbanas; Goiânia; Patrimônio sombrio; Heritage; Legends; Urban; Dark heritage; CIENCIAS HUMANAS::HISTORIA